The Epistemology of Hadith Authenticity: The Construction of Sanad from a Muslim-Western Perspective - Taufiki Ali Ilhami; A'azliansyah Farizil Anam (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2025)
This research stems from an academic problem surrounding the authenticity of hadith, which has sparked a heated debate between Islamic epistemology and modern Western epistemology. In Islamic tradition, hadith is believed to have absolute validity, which is maintained through the sanad system as a scientific and spiritual mechanism to ensure the continuity of truth from the Prophet to the ummah. Conversely, Western scholars view sanad as a socio-historical construct formed retrospectively to legitimize certain religious authorities, thus raising doubts about the authenticity of hadith. This study aims to critically analyze how the construction of sanad influences the assessment of hadith authenticity by comparing Muslim and Western epistemological frameworks. The method used is a qualitative approach with comparative-analytical library research of classical and modern works, both from hadith scholars and Orientalists. The results show that the construction of sanad is not only a historical tool for tracing transmission, but also an epistemic foundation that confirms the authority of revelation in the Islamic tradition. Thus, this study confirms that the authenticity of hadith can only be fully assessed if the sanad system is understood in the context of Islamic epistemology, which is oriented towards transcendental truth, rather than merely historical validity as in the Western perspective